REGULATORY CENTRALISM AND TERRITORIAL DISCRIMINATION: A SOCIO-LEGAL ANALYSIS OF CONSTITUTIONAL RIGHTS VIOLATIONS IN INDONESIA’S STUNTING GOVERNANCE (2018–2023) - Mhd. Ilham Armi (Domus Legalis Cogitatio, 2025)
While Articles 28B (2) and 28H (1) of the 1945 Constitution mandate non-discriminatory rights to child health, 2018–2023 IKPS data reveal that incremental national progress obscures persistent territorial discrimination, evidenced by a staggering 39.3-point gap existing between D.I. Yogyakarta and Papua’s stunting management scores. This study aims to analyze how a centralized regulatory model for stunting management has resulted in territorial discrimination, implicating the state's failure to equitably fulfill the constitutional right to health. This study employs a socio-legal approach, applying the theoretical framework of responsive regulation to evaluate stunting management policies. Longitudinal data were obtained from the IKPS for the 2018-2023 period, encompassing national trends, achievements per dimension, and inter-provincial disparities. The study presents three main findings. First, the rate of increase in the national IKPS has fluctuated and remains insufficient to achieve the 14% prevalence target by 2024. Second, there are significant inequalities among dimensions, with the education dimension consistently ranking the lowest and even experiencing a score decline of 4.11% during the observation period. Third, and most crucially, a massive territorial gap exists between the highest-achieving province (D.I. Yogyakarta, IKPS 84.8) and the lowest (Papua, IKPS 45.5), with the difference reaching 39.3 points in 2023. This gap is primarily driven by extreme disparities in the education dimension. This persistent territorial disparity is not merely a technical issue but rather evidence of systemic discrimination in the fulfillment of the constitutionally mandated right to health. The uniform, top-down regulatory model has proven unresponsive to the diversity of regional contexts, thereby perpetuating social injustice. The study concludes that to ensure children's rights are guaranteed equitably, institutional reform is necessary towards a regulatory model that is responsive, democratic, and empowers local governments to design contextual and adaptive interventions.